Perancangan Pengendali Temperatur pada Alat Pengering Makanan Berbasis IoT - Nita Nurdiana; Abdul Azis; Perawati Perawati (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
The manual drying process in sunlight is not always possible, especially in the case of cloudy weather and rain. Technological advances, especially in the field of control systems, have made it possible to perform manual tasks automatically. This dryer control design is designed to facilitate the drying process so that the food drying process can be carried out at any time. Application of laboratory experimental methods in hardware and software design. This tool uses the esp32 microcontroller as a dht22 sensor controller to detect temperature and humidity. From the results of the tests performed, the dht22 sensor can record the temperature and humidity according to the specified settings. It can be controlled manually or automatically during the development of this tool. It takes 1 hour and 25 minutes to reduce the water content of 1 kg of rice from 30 percent to 60.9 percent of the original water content. It is expected that this tool will be able to dry foods that originally took a long time to dry by hand in a short time. Intisari Proses pengeringan manual menggunakan sinar matahari tidak selalu memungkinkan, terutama saat mendung atau hujan. Kemajuan teknologi, terutama di bidang sistem kontrol, memungkinkan untuk melakukan tugas manual secara otomatis. Perancangan pengendali pengering ini dirancang untuk memudahkan proses pengeringan sehingga proses pengeringan makanan dapat dilakukan setiap saat. Penerapan metode eksperimen laboratorium dalam perancangan perangkat keras dan perangkat lunak. Alat ini menggunakan mikrokontroler esp32 sebagai pengendali dan sensor dht22 untuk mendeteksi temperatur dan kelembaban dimana pengaturan temperatur dan kelembaban dapat dilakukan secara manual atau otomatis. Dari hasil pengujian yang dilakukan, sensor dht22 dapat mendeteksi temperatur dan kelembaban sesuai dengan pengaturan yang ditentukan. Dibutuhkan waktu 1 jam 25 menit untuk menurunkan kadar air 1 kg padi dari 30 persen kadar air awal menjadi 60,9 persen. Dengan alat ini, diharapkan makanan yang semula membutuhkan waktu lama untuk dikeringkan secara manual dapat dikeringkan dalam waktu yang singkat.